ANALISIS BEBAN KERJA, STRES KERJA, DAN PENGEMBANGAN KARIER TERHADAP KINERJA SALES PROMOTION GIRL PADA PT. MITRA ANDAL SEJATI - Khairunisa, Michrum; Insan, Muhammad Yalzamul; Batubara, Soulthan Saladin (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research was conducted at PT Mitra Andal Sejati to know and analyze the effect of workload, work stress, and career development on employee performance partially and simultaneously. The sampling technique used was saturation sampling with a sample size of 40 Sales Promotion Girls. Data was collected through observation, questionnaire distribution, and documentation studies. Data analysis was conducted through SPSS 25 which includes a data quality test, classical assumption test, multiple linear regression analysis, hypothesis testing, and determination test. The results of this study indicate that simultaneously workload, work stress, and career development have a significant influence on employee performance. Workload and work stress partially have a negative and significant effect on employee performance, while career development has a positive and significant impact on employee performance.